DESAFÍOS EN LA IMPLEMENTACIÓN DEL TURISMO VIVENCIAL EN LA PROVINCIA DE LOS RÍOS - SUÁREZ PINCAY KLEBER ALBERTO (2024)
The province of Los Ríos in Ecuador has great tourism potential due to its cultural wealth and biodiversity. Experiential tourism offers authentic experiences in local communities, but faces challenges such as lack of infrastructure, public services, and community resistance to change. Experiential tourism in Los Ríos can generate economic and social development, promoting local culture and respect for the environment. It is crucial to strengthen the social fabric and attract tourists interested in authentic experiences. A mixed methodology (qualitative and quantitative) was used, including semi-structured interviews with tourism professionals and focus groups with residents and visitors from the different cantons. Structured surveys captured opinions on the impact of experiential tourism, and a thematic and statistical analysis was carried out to identify patterns and trends of experiential tourism, for community integration